Development of Auto-Sludge Removal System for Highland Irrigation - Mohd Hudzari, Haji Razali; Md.Sarwar, Jahan; Soran Jalal, Abdullah; Azizah, Endut; Noordin Asimi, Mohd Noor (2017)
Residents of rural areas in Malaysia such as aborigine use the natural water resources as the main source for water supply. The reservoir was built on the top of hilly contour area to collect water before discharged through a pipe system using gravitational force to flow down into settlements. However, the sludge that normally created from flowing down of water in the reservoir comes from foreign material such as leaves, twigs, moss and so on. It requires the resident to commute up the hill to remove the sludge’s due for reducing the sludge level in reservoir. Many of hilly reservoirs use the concept of stopper that made from the wood sheltered with the pieces of sheet and punch into the runner hole at bottom of reservoir. A lot of energy and time are required to manage this kind of irrigation systems especially at the time of rainy season. Thus, an innovation system had been conducted as the autosludge removal system that operates automatically using solar energy supply. The designs of this device are equipped with electric motors, washer rods, power supply units, power screw, limit switches, mechanical timer and automatic control box. The electrical power that generated from solar panel is connected with battery extraction in controller box which designed with electrical circuit and relay action for generating the forward and backward movement of the stopper for sludge removing process. It can operate non-stop for an hour and as a result, the user will not require climbing up the hill just for such sludge removal activity.